AN EXPERIENCE OF 42 CASES OF BRONCHOSCOPY AT SAIDU GROUP OF TEACHING HOSPITALS, SWAT - Hussain, Gulshan; Iqbal, Mahid; Khan, Sharafat Ali; Iqbal, Muhamad; Zaman, Javed (Journal of Ayub Medical College Abbottabad, 2006)
Background: The objectives of our study were to find out the frequency in terms of age and sex of the patients, type and site of foreign bodies, clinical manifestations and management with rigid ventilating bronchoscope. Methods: It was a descriptive study carried out in the department of otolaryngology and head and neck surgery at Saidu Teaching Hospital swat, and was conducted from March 2005 to March 2006. A total of 42 cases collected from March 2005 to March 2006, admitted through casualty, OPD and referred by pediatric unit. All of them subjected to bronchoscopy as an emergency as well as an elective procedure. Results: A total of 42 cases were included in the study. In 37 cases (88.09%) foreign bodies were removed successfully, while 4 cases (9.52%) were having no foreign body, only mucous plug was removed. One patient (2.32%) died due to cardiac arrest. Key words : Foreign body tracheobroncheal tree, bronchoscopy.